2006
DOI: 10.1159/000096440
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Sepsis on the Development of Allergies and Asthma in Later Childhood

Abstract: Background: Exposure to large amounts of endotoxins and other bacterial products in early childhood may protect against the development of allergic diseases later in childhood. The aim of this study was to investigate the effects of neonatal sepsis on subsequent development of asthma, allergic rhinitis, and atopic dermatitis in children. Methods: We recruited 85 children (mean age 48.67 ± 12.88 months) who had been hospitalized for sepsis in their neonatal period and their siblings (n = 85) as controls (mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 70 publications
3
21
0
Order By: Relevance
“…This meant that 12 articles were available for the final review. These studies included a total of 3669 infants with neonatal sepsis and 24 723 infants without sepsis, who were considered as controls . Of the 12 papers we included, nine investigated infants born before 34 weeks of gestational age or with a birthweight of less than 1500 g , including 3484 infants with neonatal sepsis and 23 912 infants without neonatal sepsis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This meant that 12 articles were available for the final review. These studies included a total of 3669 infants with neonatal sepsis and 24 723 infants without sepsis, who were considered as controls . Of the 12 papers we included, nine investigated infants born before 34 weeks of gestational age or with a birthweight of less than 1500 g , including 3484 infants with neonatal sepsis and 23 912 infants without neonatal sepsis.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 12 papers we included, nine investigated infants born before 34 weeks of gestational age or with a birthweight of less than 1500 g , including 3484 infants with neonatal sepsis and 23 912 infants without neonatal sepsis. A further three studies investigated infants born after at least 34 weeks of gestational age or with a birthweight of up to 1500 g, including 185 infants with neonatal sepsis and 811 infants without neonatal sepsis . Only one of the 12 studies investigated the short‐term outcome of term infants , while the other studies described long‐term outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is partially supported by studies demonstrating that children who survived neonatal sepsis were less likely to develop asthma. 39,40 MYLK plays a pivotal role in regulating both smooth muscle contractile activity and numerous functions in nonmuscle cells, 41 including leukocyte recruitment to the airways, 22 and is therefore an attractive candidate gene for atopic asthma. MLC phosphorylation is associated with smooth muscle contraction via maintenance of tight junction permeability at the apices of lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Endotoxin exposure during the post-natal period has been shown to program permanent alterations in immune system in animals that have a new contact with LPS in adult life (Ellis et al 2005, Roponen et al 2005, Kato et al 2006, Cetinkaya et al 2007). Many studies demonstrated that this exposure at low doses produces an attenuation of the febrile response in adults.…”
Section: Discussionmentioning
confidence: 99%